ANALISIS PENGARUH KINERJA KEUANGAN PERBANKAN TERHADAP HARGA SAHAM PERBANKAN TAHUN 2008 â 2010 (Studi Kasus Pada Perusahaan Perbankan Yang Go Publik Di Bursa Efek Indonesia) - Ekhsan Anggriawan, 08.05.52.0113; Setyowati, Widhy (Students Journal of Accounting and Banking, 2013)
This study aimed to analyze the influence of the financial performance of the stock price is used perbankan.variabel CAR, RORA, OEOI, EPS, LDR. This research used purposive sampling to select a sample with a sample of 29 Go Publick Banking Company in Indonesia Stock Exchange (IDX) The results of this study indicate that the CAR negative and not significant between the car and the price of the stock, RORA and significant negative effect on stock prices, OEOI significant negative effect on stock prices, EPS positive and significant effect on stock prices, LDR positive and not significant to the stock priceKeywords: STOCK PRICE, CAR, RORA, OEOI, EPS, LDR.